Effectiveness of Diversity Integration in Cosmetics Career Curriculum - JU-HSUAN YEH (Universitas Negeri Semarang, 2024)
This study investigates the effectiveness of incorporating diverse teaching methods into career development courses for students in beauty-related majors at a vocational college in Taiwan. A quasi-experimental design was employed, involving two third-year classes majoring in cosmetics application and management. The experimental group received diverse teaching strategies, while the control group followed traditional theoretical instruction. A